EXPLORING PEER-ASSESSMENT PRACTICE IN GRADUATE STUDENTS’ ACADEMIC WRITING - Dewi, Ema Wilianti; Nurkamto, Joko; Drajati, Nur Arifah (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2019)
This study aims to explore the practice of peer-assessment in academic writing. The current researchers find it urgent to investigate academic writing because it has rigid rules that can sharpen writers' critical thinking. The products of academic writing need to be assessed. Peer-assessment is one of alternatives used to assess students’ learning outcomes and monitor students’ progress in the class. This research is a case study. Data were collected from the first semester students, who joined an academic writing class, of the graduate program of a university in Surakarta. The findings show that peer assessment practice can be effective as one of the assessment tools to measure students' writing in the academic writing class. DOI: doi.org/10.24071/llt.2019.220106